Coupled Vibration of Unshrouded Centrifugal Compressor Impellers. Part II: Computation of Vibration Behavior - Dirk Hagelstein; Heinrich Hasemann; Manfred Rautenberg (International Journal of Rotating Machinery)
The increased use of small gas turbines and turbochargers in different technical fields has led to the development of highly-loaded centrifugal compressors with extremely thin blades. Due to high rotational speed and the correspondingly high centrifugal loads, the shape of the impeller hub must also be optimized. This has led to a reduction of the thickness of the impeller disc in the outlet region. The thin parts of the impeller are very sensitive and may be damaged by the excitation of dangerous blade vibrations.